1974
DOI: 10.3758/bf03334277
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of episodic memories as a function of their age

Abstract: Ninety-eight undergraduates were given a list of 20 common English nouns and told to inspect each word until a specific episodic memory associated with it came to mind, and to write a few words to identify that memory. After finishing the list, they were asked to go back and to date the episodic memories as accurately as they could. The frequency of memories as a function of their age was found to be log log linear, with the frequency inversely related to the age of memory_ It would be desirable to expose by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
364
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(383 citation statements)
references
References 3 publications
12
364
6
Order By: Relevance
“…Rubin asked young adults to think of past events related to each of over 100 cue words (e.g., cup, chair, and tree), and to estimate their age at the time of the event. To the data, Wetzler and Sweeney fitted a power function that in many investigations (e.g., Crovitz & Schiffman, 1974;Rubin & Wenzel, 1996;Rubin, Wetzler, & Nebes, 1986) has been shown to capture the distribution of memories across the life span. As discussed by Rubin and Wenzel (1996), the power function (e.g., Wickelgren, 1974Wickelgren, , 1975 implies that equal ratios of time (t 1 /t 2 ϭ t 3 /t 4 ) will result in equal ratios of recall (recall 1 /recall 2 ϭ recall 3 /recall 4 ).…”
Section: Characteristic Distribution Of Early Memoriesmentioning
confidence: 99%
“…Rubin asked young adults to think of past events related to each of over 100 cue words (e.g., cup, chair, and tree), and to estimate their age at the time of the event. To the data, Wetzler and Sweeney fitted a power function that in many investigations (e.g., Crovitz & Schiffman, 1974;Rubin & Wenzel, 1996;Rubin, Wetzler, & Nebes, 1986) has been shown to capture the distribution of memories across the life span. As discussed by Rubin and Wenzel (1996), the power function (e.g., Wickelgren, 1974Wickelgren, , 1975 implies that equal ratios of time (t 1 /t 2 ϭ t 3 /t 4 ) will result in equal ratios of recall (recall 1 /recall 2 ϭ recall 3 /recall 4 ).…”
Section: Characteristic Distribution Of Early Memoriesmentioning
confidence: 99%
“…Additionally, they were given a word-cued memory task in which 30 words were presented, and each participant was asked to produce one memory in response (cf. Crovitz & Schiffman, 1974). For each phase of memory testing, participants were asked to rate their memories on pleasantness, intensity, significance, novelty, vividness, and frequency of rehearsal.…”
Section: Effects Of Emotion On Encoding and Consolidation-mentioning
confidence: 99%
“…These investigators used the Galton -Crovitz word-cue technique [12] in which participants are asked to describe an autobiographical episode from their recent or remote past in response to single word cues. Kinsbourne and Wood found that amnesic patients were poor at recalling autobiographical events though they could retrieve generic information pertaining to these words.…”
Section: Episodic 6ersus Semantic Memorymentioning
confidence: 99%